2019
DOI: 10.1111/rda.13546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recipient oocyte source, number of transferred embryos and season on somatic cell nuclear transfer efficiency in sheep

Abstract: To improve the efficiency of somatic cell nuclear transfer (SCNT) in sheep, we investigated the effects of recipient oocyte source, number of transferred embryos and season on the pregnancy and live lamb rates for sheep somatic cell nuclear transfer embryos. Follicle‐stimulating hormone (FSH)‐stimulated ovaries produced significantly more oocytes both in total and of suitable quality for maturation culture than those without FSH treatment (from slaughterhouse). However, their in vitro maturation rates were sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A r t i c l e development and producing offspring [4,6,[10][11][12][13]. However, studies on embryo development and pregnancy rate according to oocyte sources are limited in camels.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 3 more Smart Citations
“…A r t i c l e development and producing offspring [4,6,[10][11][12][13]. However, studies on embryo development and pregnancy rate according to oocyte sources are limited in camels.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Studies on the pregnant efficiency to oocyte sources in camels reported so far have used a small number of oocytes and surrogates [4,6]. Furthermore, several studies on the efficiency of pregnancy have been reported that the in vitro matured oocytes showed decreased pregnancy rates in other mammalians, including sheep, mouse, and human [11][12][13]. Therefore, the present study used a large number of surrogates, slaughtered ovarieshouse-, and OPU-derived oocytes to reconfirm the effect of the source of oocytes on pregnant efficiency.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) sheep [21][22][23][24][25][26]; (4) pigs [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]; (5) equids-domestic horses [42][43][44][45][46] and mules [47]; (6) water buffaloes-Chinese swamp buffaloes [48,49] and Indian river/riverine buffaloes [50][51][52][53]; (7) one-humped or dromedary camels [7,[54][55][56]; (8) two-humped or Bactrian camels [57]; (9) domestic cats [58][59][60][61][62][63]; (10) domestic dogs…”
Section: Biotechnological Possibilities Of Applying the Techniques Ofmentioning
confidence: 99%